Den gjenoppståtte teatermaskin: Et postdramatisk paradoks - Arntzen, Knut Ove (Peripeti, 2021)
In the article »The Resurgent Theatre-Machine« Arntzen points out a paradox in the relationship between what he calls a Theatre of Art and a Theatre-Machine. The paradox consists in the fact that the Theatre of Art, i.e. the avant-garde, on the one hand stands in opposition to the Theatre-Machine, i.e. art as craft. On the other hand however Arntzen observes the resurgence of the Theatre-Machine inside the framework of the Theatre of Art in contemporary theatre.